2021
DOI: 10.1177/0964528421990658
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture may alleviate behavioral defects via modulation of gut microbiota in a mouse model of Parkinson’s disease

Abstract: Objective: Parkinson’s disease (PD) is a chronic neurodegenerative disease involving non-motor symptoms, of which gastrointestinal disorders are the most common. In light of recent results, intestinal dysfunction may be involved in the pathogenesis of PD. Electroacupuncture (EA) has shown potential effects, although the underlying mechanism remains mostly unknown. We speculated that EA could relieve the behavioral defects of PD, and that this effect would be associated with modulation of the gut microbiota. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Therefore, the establishment of a benign regulation mechanism of the intestinal flora of patients with SCI is of great significance for the recovery of intestinal function. EA and microbiota‐targeted techniques, such as faecal microbiota transplantation (FMT), can promote gut microbiota remodelling, which may play a role in SCI (Han et al ., 2021 ; Jing et al ., 2021 ). However, the mechanism of gut microbiota remodelling in SCI improvement is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the establishment of a benign regulation mechanism of the intestinal flora of patients with SCI is of great significance for the recovery of intestinal function. EA and microbiota‐targeted techniques, such as faecal microbiota transplantation (FMT), can promote gut microbiota remodelling, which may play a role in SCI (Han et al ., 2021 ; Jing et al ., 2021 ). However, the mechanism of gut microbiota remodelling in SCI improvement is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…After the administration of MPTP, mice showed abnormalities in locomotor ability and muscle tone, similar to the clinical manifestations of human PD [41]. Studies have demonstrated that PD mice prefer the open-eld and slow-climbing time [42,43]. The detection of behavioral de cits in PD mice using behavioral methods such as open-eld and pole-climbing can aid in the potential therapeutic evaluation of drugs for PD.…”
Section: Discussionmentioning
confidence: 96%
“…NOX2 has been identified as an upstream factor controlling oxidative stress and neuroinflammation. EA stimulation alleviates behavioral changes via modulating gut microbiota and suppressing neuroinflammation in a mouse model of Parkinson’s disease ( 57 ). A recent study demonstrated that EA affects the vagal–adrenal axis in mice ( 22 ).…”
Section: Discussionmentioning
confidence: 99%